To solve the linear-quadratic system using the elimination method, we need to eliminate one variable (either x or y) by manipulating the equations.
Given the equations:
(1) y = x^2 - 2x - 2
(2) y = 2x - 6
Since both equations are already solved for y, we can set them equal to each other to eliminate y:
x^2 - 2x - 2 = 2x - 6
Rearranging the equation:
x^2 - 4x + 4 = 0
Now we have a quadratic equation, which we can solve by factoring or applying the quadratic formula. In this case, the quadratic equation factors as:
(x - 2)(x - 2) = 0
This leads to the solution:
x = 2
Substituting x = 2 into either one of the original equations, we find:
y = (2)^2 - 2(2) - 2
y = 4 - 4 - 2
y = -2
Therefore, the solution to the linear-quadratic system is (x, y) = (2, -2).
Use the elimination method to solve the linear-quadratic system y=x^2−2x−2, y=2x−6.
1 answer